Use of vitamin E and selenium injections as supportive treatment of retained placenta in dairy cattle - Rahim, Nurul Insyirah; Hendrawan, Viski Fitri; Tuska, Habib Syaiful Arif; Agustina, Galuh Chandra (Universitas Airlangga, 2023)
The placenta is considered retained when it cannot separate from the uterus beyond the normal time limit. Physiologically, a cow's placenta comes out 3-8 hours postpartum. This study aims to determine the diagnosis and treatment of retained placenta in dairy cows using vitamin E and selenium as supportive treatment. On physical examination the patient had a body temperature of 39.9°C, was weak, unable to stand, and had decreased appetite. General examination in this case showed the following clinical symptoms: the placenta was still hanging from the vulva and there was an unpleasant odor from the vulva area. The retained placenta was removed manually, followed by flushing the uterus with 0.2% povidone iodine (in water). Antibiotic (Colibact bolus) were introduced into the uterus and penicillin-streptomycin was injected intramuscularly along with vitamin E and selenium as supportive treatment. The results showed that the cow recovered and returned to estrus 14 days after therapy. It could be concluded that injections of vitamin E and selenium helped restore the estrous cycle in cows with retained placenta.